Extension of the distribution of the migratory range of the “Black-fronted Ground Tyrant” Muscisaxicola frontalis (Aves: Tyrannidae) in Peru - Alcocer, Renzo (2011)
We extent the migratory range of distribution and elevation of Muscisaxicola frontalis (Black-fronted Groundtyrant), Austral migrant reported previously only in the Southern region of the country. The species was observed in rocky slopes near Polylepis flavipilla (Rosaceae) woodlands at 4450 m of altitude, in the Huancavelica Department.